Tokenization in real estate : opportunities and challenges - Schmid, Elena; Truebestein, Michael; Aepli, Matthias Daniel (Springer, 2024)
Traditionally, real estate has been burdened by challenges such as illiquidity, limited accessibility, opacity, complex transactions, high costs, and substantial capital requirements. However, tokenization emerges as a potential solution to many of these issues. In this book, the authors thoroughly investigate the innovative concept of tokenization in the real estate domain. Tokenization involves digitizing real estate assets and ownership, complemented by fractionalization, facilitated through blockchain technology. The book elucidates the fundamental principles, technologies, opportunities, and impediments associated with real estate tokenization. To fully capitalize on the theoretical advantages, the book furnishes specific recommendations for the overall market landscape and active participants, providing crucial guidance to encourage wider adoption and successful realization of the benefits offered by tokenized real estate.
Keywords: Real property -- Finance.; Blockchains (Databases); elektronické knihy; electronic books